EDUCATION ON THE ROLE OF PARENTS IN THE IMPORTANCE OF CHILDREN'S EDUCATION IN THE BADUY TRIBE COMMUNITY - Furtasan Ali Yusuf; Jaka Wijaya Kusuma; Hadi Kurniawanto; Hamidah Hamidah; Miftahudin Miftahudin; Sigit Auliana; Fatari Fatari; Munawaroh Munawaroh (International Journal of Engagement and Empowerment, 2023)
This activity is carried out to make an understanding of learning by providing socialization or explanation and motivation about how important education is in the family, as well as awaken the potential from within children about how to motivate adolescents to continue higher education. It is hoped that a good level of education can improve the quality of human resources so that development can run well. The method of implementing this activity is by providing socialization of understanding that contains motivation to the community in the Baduy Tribe Environment. The results of this activity are expected to increase parents' understanding that education is very important so that children can be motivated to continue their studies and increase human resources in the environment